Non‐uniform changes of growing conditions for sweet cherry trees responses to climate warming in main production regions of China. (30th November 2022) - Sun, Wanxia; Ren, Ruixuan; Liu, Yangtai; Wang, Jiyuan; Wang, Li; Liu, Xunju; Jiu, Songtao; Wang, Shiping; Zhang, Caixi
Abstract: Given the strong sensitivity of sweet cherry trees to air temperature and the foreseeable warming under future climates, it becomes urgent to analyse spatiotemporal variability of growing conditions in main production areas of China. Here, we estimated changes of three climate metrics, that is, winter chill, heat accumulation and the risk of spring frost events, by using 22 global climate models over the historical and future (represented by central years 2050s and 2085s) time stages. Statistically downscaled daily maximum and minimum temperatures at 14 sites under representative concentration pathway (RCP) 4.5 and 8.5 scenarios were used. The results show a general increase of available winter chill for most sites in Bohai and Lanzhou–Lianyungang Railway line agro‐climatic zones, and the increase in chill accumulation could reach up to 15.2% in these regions for RCP4.5 by 2085 s. However, the most dramatic winter chill decrease is projected to occur in the southwest region under the RCP8.5 scenario by 2085 s. Additionally, the increase rate of heat accumulation during the forcing period shows spatially consistency, and the most pronounced increase is found in the RCP8.5 by 2085 s. In the north region, median heat accumulation increases by 17.5%–21.0% in the 2050 s under RCP4.5. Similar increasing range could be found in the southwest station. High frost risk areas are found in the southwestern region for both baseline and future climate scenarios. Across the 14 study sites, Mengzi and Kunming have the highest meteorologically defined risk of spring damaging frost with accumulated 335 growing degree days (GDDs) and 264 GDDs before the last spring frost event, respectively. Overall, this study provides projected characteristics of site‐specific growing conditions for sweet cherry trees in main production regions. The results could be useful for decision‐making such as selection of appropriate species and varieties in adapting to future warming. Abstract : Map of 14 representative sites of the main production area for sweet cherry in China. The area is represented by four regions: the Bohai Bay region in the east, sites along the Lanzhou–Lianyungang Railway line in the north, the high‐altitude climatic region in the southwest and the Yangtze River Delta region in the south.